Video On Demand System For Heterogeneous Wireless Mobile Networks - Al-Omari, Saleh Ali Khattap (2013)
In recent years, the services of the Video on Demand (VOD) system have taken place with the improvement of the high-speed networking and enhancement of the digital video technology. The VOD system allows users to select their desired videos from a remote server, so that they can watch them instantly anytime and anywhere through public communication networks. Currently the challenge of the VOD system is to provide a seamless video access to different type of devices with a small service delay in the existing heterogeneous network environments, such as WIMAX network. There are many issues need to be tackled in designing a VOD system including the system architectures, broadcasting techniques, caching techniques, transitions between different networks, and heterogeneous mobile devices. This thesis presents a new system architecture called Video on Demand system architecture for Heterogeneous Mobile Network (VODHMN) environment. This system architecture supports VOD services for heterogeneous devices with a different capability through different networks with a limited broadcasting bandwidth. The VODHMN system architecture introduces two new components that are consist of Local Media Forwarder (LMF) and Global Media Forwarder (GMF) components as compared to the existing architecture. Both of these components can cope with the wireless environment in term of connectivity.